Survivorship Issues in Testicular Cancer (Canadian Oncology Today, 2024)
Testicular cancer (TC) is the most prevalent tumor in young men aged 15–40 years, with an annual incidence of 3–11 new cases per 100,000 males in Western countries. In 2020, the International Agency for Research on Cancer reported 74,458 newly diagnosed cases of TC globally. The etiology of TC is complex and includes both genetic and environmental factors. The prognosis of TC is excellent with a >90% cure rate and a >95% 5-year survival rate with appropriate treatment. Treatments for TC include active surveillance, chemotherapy, radiotherapy, and retroperitoneal lymph node dissection, depending on the clinical stage and tumor subtype. It is crucial that patients receive information on the diagnosis, therapeutic management options, consequences of treatments, and surveillance protocols, which allows the patient to play an active role in the decision-making process. Fear of recurrence often affects TC survivors. Therefore, it is essential to fully involve the patient in the choice of the treatment to ensure an optimal compliance, especially when selecting the active surveillance strategy. In the modern era, in light of the excellent outcomes achieved in TC management, one of the high priorities is to deliver curative treatments while minimizing long-term toxicity. This focus can have a positive impact on quality of life and life expectancy of TC survivors.